2012
DOI: 10.1007/s00449-012-0797-y
|View full text |Cite
|
Sign up to set email alerts
|

Metallic silver nanoparticle: a therapeutic agent in combination with antifungal drug against human fungal pathogen

Abstract: Silver nanoparticles (Ag-NPs) are known to have inhibitory and fungicidal effects. Resistance against fungal infection has emerged as a major health problem in recent years, which needs great and immediate concern. Here, we report the extracellular biological synthesis of silver nanoparticles through a simple green route approach using a marine mangrove (Rhizophora mucronata) and silver nitrate. Aqueous extract of marine mangrove helped in reduction and was used as capping agent in biological synthesis. Nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(35 citation statements)
references
References 50 publications
4
31
0
Order By: Relevance
“…Evidence to date indicates that the plant extract synthesized silver nanoparticles have been shown to possess broad spectrum antibacterial activity against Gram-positive and Gram-negative bacteria including multi drug resistant human pathogens (Das et al, 2013;Gopinath et al, 2012;Nabhikan et al, 2010;Prakash et al, 2013;Sathishkumar et al, 2009;Saxena et al, 2010). Moreover, these phytosynthesized silver nanoparticles have also been shown to be effective against fungal and yeast pathogens (Singh et al, 2013). Dipankar and Murugan (2012) and Raghunandan et al (2011b) have reported the antioxidant activity of plant extract derived silver nanoparticles.…”
Section: Biomedical Applications Of Plant Extract Synthesized Silver mentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence to date indicates that the plant extract synthesized silver nanoparticles have been shown to possess broad spectrum antibacterial activity against Gram-positive and Gram-negative bacteria including multi drug resistant human pathogens (Das et al, 2013;Gopinath et al, 2012;Nabhikan et al, 2010;Prakash et al, 2013;Sathishkumar et al, 2009;Saxena et al, 2010). Moreover, these phytosynthesized silver nanoparticles have also been shown to be effective against fungal and yeast pathogens (Singh et al, 2013). Dipankar and Murugan (2012) and Raghunandan et al (2011b) have reported the antioxidant activity of plant extract derived silver nanoparticles.…”
Section: Biomedical Applications Of Plant Extract Synthesized Silver mentioning
confidence: 99%
“…The antibacterial activity of silver nanoparticles has been performed against Gram-positive and Gram-negative bacteria (Ahmad et al, 2011;Ghosh et al, 2012;Kora et al, 2012;Nabikhan et al, 2010;Sankar et al, 2013;Sathishkumar et al, 2009;Saxena et al, 2010;Veerasamy et al, 2011). Few studies have been carried out using multi drug resistant pathogens (Das et al, 2013;Gopinath et al, 2012;Prakash et al, 2013) and fungal pathogens including Candida albicans (Singh et al, 2013). Interestingly, plant extract synthesized silver nanoparticles have also demonstrated effective inhibitory activity against multi drug resistant Gram-negative nosocomial pathogens (Prabakar et al, 2013), spore forming bacteria (Patil et al, 2012b), water borne pathogens (Krishnaraj et al, 2010) and aquatic pathogens (Umashankari et al, 2012).…”
Section: Antimicrobial Activity Of Plant Extract Synthesized Silver Nmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioreduction potential of plant extracts is comparatively higher than the microbial and fungal methods; many researchers support this hypothesis (Iravani, 2011;Kanan et al, 2011). Researchers have reported the supremacy of green nanoparticles over several applications of polar and non polar plant extracts such as antifungal activity (Dipankar and Murugan, 2012;Singh et al, 2013), antibacterial activity (Gopinath et al, 2012;Satishkumar et al, 2012) and anticancer activities (Satyavani et al, 2011;Jacob et al, 2012).…”
Section: Light Scattering and Zeta Potentialmentioning
confidence: 99%
“…of AgNPs did not affect any of the tested fungal pathogens (Table 3). Recently, Singh et al [33] have evaluated the in vitro antifungal activity of Rhizophora mucronata synthesized AgNPs along with nanoformulations of fluconazole and itraconazole against Candida albicans, Aspergillus fumigatus, Aspergillus flavus, Cryptococcus neoformans in which fluconazole formulated AgNPs showed better antifungal activity than itraconazole formulated one. But both formulations showed pronounced antifungal activity against Candida albicans, however, other fungal pathogens also showed moderate activity.…”
Section: Antifungal Activitymentioning
confidence: 99%